Minimum detectable change and false positive rates of the vestibular/ocular motor screening (VOMS) tool: an NCAA-DoD care consortium analysis. (10th November 2021) - Eagle, Shawn R.; Ferris, Lyndsey M.; Mucha, Anne; Sinnott, Aaron; Marchetti, Gregory; Trbovich, Alicia; Port, Nicholas; Clugston, Jay; Ortega, Justus; Collins, Michael W.; Broglio, Steven P.; McAllister, Thomas; et al.
ABSTRACT: Objective: To derive minimum detectable change (MDC) across individual Vestibular-Ocular Motor Screening (VOMS) items and VOMS overall score in 17–25 years old collegiate athletes and to examine false positive rates. Method: Participants (n = 378) completed VOMS pre-season for two consecutive years. MDC was identified for individual VOMS symptom items and NPC distance (cm). Both total and change methods of VOMS scoring were included in analysis. Results: Regarding total scoring, MDC for ocular VOMS symptom items was 1 and MDC for vestibular VOMS symptoms items was 2. MDC for NPC was 4 cm and for VOMS overall score was 10. Regarding change scoring, MDC for each VOMS symptom item was 1, and for VOMS overall score was 8. False positives ranged from 5.3% to 15.9%. Conclusions: This study presents MDCs for each VOMS item and overall VOMS score, using total and change scoring. These values can be considered true change outside measurement error with 95% confidence in a 17–25 year old collegiate athlete population.